THERAPY WITH PLASMASUBSTITUDE SUBSTANTIONS IN WOMEN WITH IMMUNOLOGICAL STERILITY - Kotlik, Yu.A.; Grіschenko, N.G. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The article presents data of clinical observations and of some immunological researches of 60 women, 30 from which demonstrated immunological sterility, and others 30 were include in control group. The data of immunological researches of women with immunological barrenness has demonstrated risingpercentage Т-hel-perscells, fallen percentage Т-suppressors cells and rising immunoregulatore index. The raised contents of circulating immune complexes, heterophil hemolysins and lymphocitotoxic antibodies in the serum. In women with therapy of plasmasubstitudes substations after 30 days  we fixed normalization of parameters of a humoral link of immunity.